Preparation and Voltammetric Studies of Titanium (IV) Phosphate Modified with Silver Hexacyanoferrate to a Voltammetric Determination of L-Cysteine - Cumba, Loanda Raquel [UNESP]; Bicalho, Urquisa de Oliveira [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Electrochemical Science Group, 2012)
In this work, a novel Titanium (IV) Phosphate (TiPh) composite was prepared using a easily methodology of the synthesis. A preliminary characterization of the precursor and resulting materials was defined using spectroscopic and voltammetric techniques. As a second step, TiPh was reacted with silver ions (TiPhAg) and subsequent hexacyanoferrate was added (TiPhAgHCF). The electrochemical behaviour of the composite (TiPhAgHCF) was verified by means of a graphite paste electrode using cyclic voltammetry in a potential range of 0.2 to 0.9 V (vs Ag/AgCl). The cyclic voltammogram of the modified electrode containing (TiPhAgHCF) exhibited a single redox couple. The redox couple present a formal potential (E-theta) of 0.77 V vs Ag/AgCl (KNO3 1.0 mol L-1; v = 20 mV s(-1)) and ascribed to the [Fe-II(CN)(6)] / [Fe-III(CN)(6)] processes. In a electroanalytical study, the peak located at 0.77 V present a sensitive response to L-cysteine. The modified graphite paste electrode showed a linear range from 2.0x10(-4) to 9.0x10(-3) mol L-1 for the determination of L-cysteine with a limit detection of 3.34x10(-4) mol L-1 and relative standard deviation of. 5% (n = 3) and amperometric sensitivity 10.34x10(-3) A mol L-1. The modified electrode was electrochemically stable and showed excellent reproducibility.
Keywords: Titanium (IV) phosphate; cyclic voltammetry; L-cysteine